Prostitution og oprejsning - Pedersen, Camilla Brokholm (Dansk Teologisk Tidsskrift, 2024)
In this article, I conduct a diachronic cultural-historical analysis of the phenomenon of prostitution in pagan and Christian antiquity. My prime focus is how the spread and consolidation of Christianity in the Greco-Roman world effected the social attitudes towards prostitutes and their prospects in terms of social and spiritual rehabilitation. I begin with an introduction to the issue of prostitution in pagan roman antiquity, highlighting some of the social, legal, and economic aspects pertaining to it. I then examine the perspectives on social and spiritual rehabilitation in The Shepherd of Hermas and the stories of the repenting prostitutes, Mary of Egypt, and Pelagia of Antioch. Finally, I discuss and sum up the differences between the pagan and Christians attitudes towards prostitutes and their rehabilitation